The Effectiveness of Cognitive-Behavioral Therapy (CBT) Based on Kesh's Eight-Step Model on Body Image and Self-Esteem among Married Women in Birjand - Zahra Khayati (Journal of Global Pharma Technology, 2017)
Background and objective: In recent decades, body image problems have been considered by clinical practitioners and some therapeutic methods have been designed for them. At present, a widespread attention is paid to cognitive-behavioral therapy, because this type of treatment provides clear and complete methods for intervention and measurements. The present study was done to investigate the effectiveness of cognitive-behavioral therapy based on Kesh's eight-step model on the body image and sexual self-esteem among married women in Birjand. Method: This was a semi-experimental study which was carried out on 30 married women referred to Omid Counseling Clinic in Birjand. The subjects were selected through convenience and voluntary sampling method and randomly assigned to experimental group (n=15) and control group (n=15). The experimental group received eight 90-minute sessions of training techniques of cognitive-behavioral therapy based on Kesh's eight-step model. The instruments to collect data were Multidimensional Body Self-Relations Questionnaire (MBSRQ) and Zeanah and Schwarz Sexual Self-Esteem Inventory for Women (SSEI-W). To analyze data, multivariate analysis of covariance in the environment of SPSS software (ver. 21) was used. Findings: The results of covariance analysis showed that there was a significant difference between the mean scores of body image in experimental and control groups based on group membership in the post-test with 99% confidence (P<0.01), and the intervention effect was 0.49. Also, there was a significant difference between the mean scores of sexual self-esteem in experimental and control groups based on group membership in the post-test with 99% confidence (P<0.01), and the intervention effect was 0.38.ConclusionOverall, it can be said that the cognitive-behavioral therapy based on Kesh's model can be used as an appropriate intervention method to treat problems related to body image and sexual self-esteem.Keywords: Cognitive therapy based on Kesh's eight-step model, Body image, Sexual self-esteem.